THE EFFECT OF WORK ENVIRONMENT, LEARNING STRATEGIES AND HEAD OF MILITARY TRAINING ON THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN SEKAYU DISTRICT, MUSI BANYUASIN DISTRICT - Cik Molek; Indawan Indawan; Omar Hendro (KOLEGIAL, 2020)
This study aims to determine the effect of work environment, learning strategy and principal leadership on teachers' performance in public Elementary Schools in Sekayu District, Musi Banyuasin District. The research design used is associative or correlational research because it connects independent variables with dependent variables. The analysis model used in this study is multiple linear regression analysis. The population was 104 and a sample of 83 respondents were Elementary School Teachers in Sekayu District. The study concluded, first, the Work Environment, Learning Strategy and Principal Leadership had a significant effect on the Performance of Teachers of Public Elementary Schools in Sekayu District, Musi Banyuasin District. Second, there is a significant relationship between Work Environment Variables on Teacher Performance Variables. Third, Learning Strategies on Teacher Performance. Fourth, there is a significant relationship between Principal Leadership Variables on Teachers' Performance in Public Elementary Schools in Sekayu District, Musi Banyuasin District.